Design and Implementation of Virtual Xinjiang Carpet Pattern Museum - Peng, Hong; Zhang, Mingmin (International Journal of Virtual Reality, 2012)
Xinjiang carpet design is the art treasure among the treasure house of Chinese culture. Virtual museum is the function carrier which collects and promotes the national culture. Through the analysis of the virtual experience interactive technical characteristic, the paper proposed "the scene roaming: interactive control operation: interactive content show" design method. And realized the interactive experience technology based on the users and the products through the unity3D, and also enriched the display mode of virtual Xinjiang carpet design museum.